Two new species of African suckermouth catfishes, genus Chiloglanis (Siluriformes: Mochokidae), from Kenya with remarks on other taxa from the area - Schmidt, Ray C.; Bart, Henry L. Jr; Nyingi, Wanja Dorothy (Zootaxa, 2015)
Recent expeditions in Kenya and examination of existing collections confirmed the presence of two undescribed Chiloglanis species and revealed previously unknown diversity within the Athi River system. The two new species are easily distinguished from described congeners in the area by external morphology, allopatric distributions, and genetic markers. Chiloglanis kerioensis sp. nov., is restricted to the Kerio River system and is the only known suckermouth catfish from the Lake Turkana basin. Chiloglanis devosi sp. nov., is known only from the type locality, the Northern Ewaso Nyiro (Ng’iro) below Chanler’s Falls. In addition to these two new species, this study confirmed the presence of an undescribed Chiloglanis sp. occurring sympatrically with Chiloglanis brevibarbis in the Tsavo River. A dichotomous key for identifying all described Chiloglanis species found within Kenya is presented along with comments.